2012
DOI: 10.2500/ar.2012.3.0030
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between IL-17A and Macrophages or MUC5AC in Eosinophilic Chronic Rhinosinusitis and Proposed Pathological Significance

Abstract: Recently, some researchers have reported that macrophages and neutrophils were related to severe asthma. Mucus hypersecretion and persistent airway inflammation result from increased expression of mucin gene (MUC5AC). Eosinophilic chronic rhinosinusitis (ECRS) is considered as intractable rhinosinusitis. From the viewpoint of “one way one disease,” we examined whether ECRS is associated with infiltrating macrophages, neutrophils, their promotive factors, and MUC5AC. We examined 21 nasal polyps with CRS. Each s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…16 There was a study suggesting that infiltrating macrophages, IL-17A, and a mucin gene (MUC5AC), as well as eosinophils could have roles in the development of eosinophilic CRS. 17 However, in the actual clinical setting of the authors, eosinophilic inflammation was less likely to be correlated with surgical outcomes. There were reports showing differences of the cellular composition of NP between the Koreans and Westerners.…”
Section: Discussionmentioning
confidence: 96%
“…16 There was a study suggesting that infiltrating macrophages, IL-17A, and a mucin gene (MUC5AC), as well as eosinophils could have roles in the development of eosinophilic CRS. 17 However, in the actual clinical setting of the authors, eosinophilic inflammation was less likely to be correlated with surgical outcomes. There were reports showing differences of the cellular composition of NP between the Koreans and Westerners.…”
Section: Discussionmentioning
confidence: 96%
“…ECRS has significantly higher association with asthma and higher incidence of aspirin sensitivity 13,14 . In our study, bronchial asthma and aspirin sensitivity were found to be more common in patients with eosinophilic polyps; the association of bronchial asthma and eosinophilic polyps was weak; and no significant statistical association between eosinophilic polyps and aspirin sensitivity.…”
Section: Sakuma Et Al Concluded That Blood Eosinophilia Asthma Complmentioning
confidence: 97%
“…6,7 Emerging evidence suggests a role for ATX-LPA in facilitating lymphocyte migration into lymphoid and chronically inflamed nonlymphoid tissues. 36,37 Thus, considering that inflammatory cell infiltration or exudation into the sinus mucosa appears to play an important role in the development of CRSwNPs or CRSsNPs, [38][39][40] we suggest that LPA, via LPA1-3, may play a significant role in inducing and/or sustaining the massive infiltration of inflammatory cells in human sinus mucosa. These suggestions are supported by the role of LPA receptors in airway inflammatory disease studied in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 95%